PERAN STRATEGIS MANAJEMEN DAN ARAH ORGANISASI DALAM MENINGKATKAN KUALITAS PENDIDIKAN ISLAM - Moch. Misbahul Alam; Haifa; Meli Handayani; Syabilananta Khairunnisa; Mardiyah (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the strategic role of management and organizational direction in improving the quality of Islamic education at SMP Buana Waru. Using a qualitative approach and case study method, this research explores how the school leadership and management structure direct the vision and policies of the school to meet the challenges of modern Islamic education. Observational results reveal that strategic planning, the involvement of all organizational components, and leadership rooted in Islamic values are key factors in shaping a high-quality educational environment. The study recommends enhancing managerial capacity and internal organizational synergy as strategic steps toward continuous quality improvement in Islamic education